Preparation of chiral β-hydroxytriazoles in one-pot chemoenzymatic bioprocesses catalyzed by Rhodotorula mucilaginosa - Aguirre Pranzoni, Celeste Beatriz (2019)
Chemoenzymatic strategies for the preparation of enantiopure β-hydroxytriazoles were designed. These and other related compounds are particularly relevant because of their antitubercular bioactivities and as β-adrenergic receptor blockers. The ability of Rhodotorula mucilaginosa LSL to stereoselectively reduce prochiral ketones coupled to copper(I)-catalyzed azide-alkyne cycloaddition was exploited. The reactions were performed in aqueous medium and at room temperature. R. mucilaginosa LSL offered the advantage of internal redox cofactor recycling. Notably, the biocatalyst was compatible with all the chemicals required namely sodium azide, copper sulfate and alkynes and showed a broad substrate scope reducing small-bulky and bulky-bulky ketones stereoselectively. Considering this, two one-pot processes were assessed to synthesize enantiopure (R)-β-hydroxytriazoles. A one-pot, three-step sequential transformation allowed obtaining enantiopure products up to 65% yield starting from α-chloro arylketones. On the other hand, with α-bromo arylketones, a one-pot cascade process furnished the same products in ca 80% isolated yield.